The Effect of Small-Sided Games Training on the Short Passing Ability of Bhanu Football Academy Players Aged 13–15 Years in Mukomuko - Ari Sucipto Suarman; Dian Pujianto; Yahya Eko Nopiyanto (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Short passing ability is a fundamental skill in football, particularly for youth players. One training method considered effective and appropriate for young athletes is Small-Sided Games, as it increases player involvement and creates game situations similar to actual match conditions. This study aimed to determine the effect of Small Sided Games training on the short pass ability of players at Bhanu Football Academy aged 13–15 years in Mukomuko. Methods: This study employed an experimental method using a one-group pretest–posttest design. The sample consisted of 30 Bhanu Football Academy players aged 13–15 years in Mukomuko, selected through purposive sampling. The Johnson Soccer Test was used to measure short passing ability before and after the intervention. The Small-Sided Games training program was conducted for six weeks with a frequency of three sessions per week. Data were analyzed using normality tests, homogeneity tests, and a paired sample t-test at a significance level of 0.05. Result: The results showed an increase in the mean short passing score from 28.43 in the pretest to 38.50 in the posttest. The t-test results indicated that the calculated t value (–38.832) was lower than the t table value (–1.699), demonstrating a significant effect of Small-Sided Games training on short passing ability. The improvement percentage reached 35.40%. Conclusion: Small-Sided Games training is effective in improving short passing ability among football players aged 13–15 years. This training method can be recommended as an alternative approach in youth football development programs to enhance technical skills.